Cor, natureza e conhecimento no curso Aristotélico Jesuíta conimbricense (1592‑1606) - Maria da Conceição Campos (Ideia, 2016)
Unified by the theoretical and hermeneutical arch that links physics to metaphysics, the three subjects here analysed, belonging to the famous Commentarii Collegii Conimbricensis Socíetatis lesu (1592-1606) - colour, nature and knowledge - strike the reader by their modernity. The first, reveals Coimbra productivity, regarding Manuel de Góis' theory of colours, so similar to Goethe's; the second, underlines ali the aesthetical possibilities the Coimbra Commentaries may confer to some theoretical domains as anthropology, cosmology or even science; lastly, after studying a theological theme that pertains to the doctrine of the knowledge, "separation", to the reader is proposed a surprisingly interpretation: the Cartesian tone ofthis precise theme.